Abnormal reproductive morphology in two species of spiny lobster: Jasus edwardsii and Jasus paulensis. (26th June 2015) - Linnane, Adrian; Pere, Anthony; Gardner, Caleb; Thellier, Thibaut
Abstract : Jasus edwardsii and Jasus paulensis are two species of spiny lobster that are distributed across south-eastern Australia and isolated islands of the southern Indian Ocean, respectively. We present rare examples of abnormal reproductive morphology in both species. For Jasus edwardsii, this included a female lobster captured in South Australia, which, in addition to the normal pair of gonopores at the base of the third pair of pereiopods, also exhibited a second a pair of gonopores on the coxopodites of the fourth pair of pereiopods. In Tasmania, a male individual exhibited the specialized pincer on the right propopodite, normally only observed in females. The frequency of abnormal morphological reproductive characteristics appeared higher in Jasus paulensis . This included 14 individuals that exhibited a range of additional and abnormal gonopore locations in both males and females. We discuss the findings in relation to rare cases of gynandromorphism in crustaceans.